Case Report: Globus Pallidus Internus (GPi) Deep Brain Stimulation Induced Keyboard Typing Dysfunction - Wong, Joshua K.; Armstrong, Melissa J.; Almeida, Leonardo; Wagle Shukla, Aparna; Patterson, Addie; Okun, Michael S.; Malaty, Irene A. (Frontiers in Human Neuroscience, 2020)
Introduction: Typing on a keyboard requires complex collaboration between visuospatial/procedural memory, language and motor function. The impaired ability to type, independent of motor deficits, apraxia or aphasia has been coined “dystypia”. Case presentation: A 68-year-old woman with a history of blepharospasm, oromandibular and segmental dystonia underwent bilateral pallidal DBS because of a waning response to botulinum toxin therapy. Following DBS, she discovered she no longer “remembered” how to type fluidly and had to “hunt and peck” for letters on the keyboard. This issue persisted at two-year follow-up. The patient underwent serial typing tests with the DBS ON versus OFF. Post-operative lead reconstruction was performed using Lead-DBS. Volume of tissue activation (VTA) modeling was combined with whole brain tractography. Results: Typing improved when the device was switched to the DBS OFF state. Cortical mapping revealed strong modulation of the right angular gyrus, left calcarine fissure and left cuneus. There was also activation of bilateral supplemental motor areas and superior parietal gyri. Discussion: Shared lesion topography analysis of dystypia cases in the literature has suggested involvement of the superior longitudinal fasciculus (SLF). The SLF involves the superior parietal lobe, angular gyrus, supramarginal gyrus, and arcuate fasiculus. Our patient’s connectivity pattern suggested SLF involvement. The improvement in OFF state typing and her imaging together suggested that the dystypia in her case was a stimulation-induced side effect. Conclusion: Dystypia is a rare side effect of DBS therapy and may be associated with SLF involvement.